FACTORS INFLUENCING THE PERFORMANCE OF FINANCIAL ADMINISTRATION OFFICERS IN SERDANG BEDAGAI REGENCY WITH MOTIVATION AS VARIABLES MODERATING - M., Ariando Sait Simanjuntak (International Journal of Public Budgeting, Accounting and Finance, 2018)
The purpose of this study is to know and analyze the influence of competency, education and training, utilization of information technology, and mental attitude to the performance of financial administration Officers and motivation as a moderating variable in Serdang Bedagai Regency. The type of research based on the level of explanation is associative research that is causal. The population in this study is the financial administration Officers in 47 SKPD in the Government of Serdang Bedagai Regency, so the population amounted to 47 people. The research method using census method, the entire population in this study used as sample research. Methods of data analysis using multiple linear regression analysis with F test, t test and residual test for moderating variables. The results of this study indicate that competency, education and training, utilization of information technology, and mental attitude simultaneously and partially affect the performance of SKPD financial administration Officers at the Government of Serdang Bedagai Regency. Motivational variables are able to moderate the relationship of competency, education and training, utilization of information technology, and mental attitude to the performance of SKPD financial administration Officers.